The impact of teacher attitudes and beliefs about large-scale assessment on the use of provincial data for instructional change - Derek T. Copp (Arizona State University, 2016)
In the quest to improve measured educational outcomes national governments across the OECD and beyond have instituted large-scale assessment (LSA) policies in their public schools. Controversy almost universally follows the implementation of such testing, related to such topics as: a) the uncertain quality of the tests themselves as psychometrics measures; b) the uses to which the data can and should be put; c) the unintended consequences of test-preparation activities and resulting score inflation; and d) the effects of high-stakes tests on students. Debates of this nature naturally involve and impact the attitudes and opinions of teachers related to their collection and use of these data. This paper examines the impact of these attitudes using both the qualitative and quantitative data from a large-scale research study on Canadian provincial assessment. Data were collected from nation-wide teacher surveys as well as interviews with teachers, administrators and district-level staff. Results show that teacher attitudes about these assessments are strongly correlated to classroom-level instructional change. Three attitudinal factors have significant effects on teaching (to) the provincial curricula, yet none significantly affects the use of less constructive instructional strategies also known as 'teaching to the test.' Specifically, the belief that large-scale assessment data have more appropriate uses and the belief that these data could lead to school improvement were significant factors in facilitating change. The implications of these findings are profound in that large-scale assessment policy cannot succeed even by its own standards without more buy in from teaching professionals.